Utilization of Animated Videos in Stimulating Listening and Speaking Skills in Early Childhood - Fauzi, Apriliana Nurulita Nur; Pamungkas, Joko; Hayati, Nur; Christianti, Martha (FKIP Universitas Lampung, 2024)
Utilization of Animated Videos in Stimulating Listening and Speaking Skills in Early Childhood. Objective : This study investigates the use of animated videos as a learning medium to stimulate listening and speaking skills in early childhood education. The research aims to highlight their effectiveness in fostering foundational language abilities. Method: Using a literature review methodology, 15 studies were selected systematically from 100 initial sources published between 2014 and 2024, based on strict inclusion and exclusion criteria. Data were analyzed qualitatively using thematic analysis to identify key patterns and insights. Findings: Findings reveal that animated videos significantly enhance listening skills, with children progressing from basic levels to advanced competencies. Speaking skills are also improved through vocabulary enrichment and better communication, encouraging children to express their ideas more effectively. Animated videos cater to diverse learning styles, increase attention spans, and motivate children to actively participate in learning activities. Specific examples include the use of animated videos to improve literacy skills, foster early numeracy, and promote character education through interactive storytelling. Additionally, this media provides engaging, enjoyable, and interactive learning experiences that help sustain children’s interest and focus. Conclusion: Animated videos not only improve children’s comprehension and speaking abilities but also encourage active engagement, making them a highly relevant tool in early childhood education. Further research is recommended to explore their applicability across broader educational contexts and age groups, ensuring their potential is maximized for diverse learners. Keywords: animated video, early childhood, listening skills, speaking skills.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024125